The purification, structural characterization and antidiabetic activity of a polysaccharide from Anoectochilus roxburghii. Issue 4 (21st April 2020) - Liu, Yuntao; Tang, Tingting; Duan, Songqi; Li, Cheng; Lin, Qinlu; Wu, Hejun; Liu, Aiping; Hu, Bin; Wu, Dingtao; Li, Suqing; Shen, Li; Wu, Wenjuan
Abstract : Anoectochilus roxburghii, a traditional Chinese medicinal herb, has been widely used for treating numerous chronic diseases. Abstract : Anoectochilus roxburghii, a traditional Chinese medicinal herb, has been widely used for treating numerous chronic diseases. In this study, a polysaccharide from A. roxburghii (ARPs-p) was purified by anion exchange and size exclusion chromatography. The structural characteristics of ARPs-p were systematically investigated for the first time via numerous chromatographic techniques, periodic acid oxidation, Smith degradation, methylation analysis, FTIR spectroscopy and 1D/2D NMR spectroscopy. The results showed that ARPs-p is a heteropolysaccharide with a molecular weight of 97 kDa; it consists of 97.75% glucose, 1.2% galactose and trace amounts of galacturonic acid, and its backbone structure is composed of →3)-β-d -Glc p -(1→ with some branching points at O-6 linked to non-reducing end units or 6-O-linked Glc p units. Furthermore, streptozotocin (STZ)-induced diabetic mouse experiments suggested that ARPs-p has excellent antihyperglycemic, antioxidant and antihyperlipidemic activities, in which 1, 3-β-d -glucan, the main component of ARPs-p, plays a vital role.